Teachers as caregivers of grieving children in school in the post-COVID-19 era: using the self-determination theory to conceptualize teachers' needs when supporting grieving children's mental health - Frei-Landau, Rivi (Frontiers in Pediatrics, 2024)
Background It has been estimated in recent studies that more than 1.5 million children worldwide lost a caregiver due to the COVID-19 pandemic. Childhood bereavement is associated with heightened risks of impaired academic and social performance, mental health issues, substance use disorders, and higher mortality rates. Yet children may receive insufficient support post-loss. Although the role of school psychologists in supporting grieving students has been examined, little is known about the role of teachers in this context. Specifically, knowledge about teachers' needs when supporting bereaved children is lacking. Objective The study's aim was to explore teachers' needs, drawing upon a well-established framework—self-determination theory (SDT)—which focuses on three human needs considered essential for optimal functioning: autonomy, competence, and relatedness. Methods Employing a qualitative approach, 36 teachers were interviewed about their needs when supporting grieving students. Interviews were transcribed and then analyzed using thematic content analysis. Results Analysis revealed three SDT-related needs: knowledge (theory- and practice-related), acknowledgment, and support (emotional and practical). Conclusions The findings enhance our theoretical understanding of childhood bereavement and may promote policy changes that ensure teachers' needs satisfaction. Its significance lies in the basic premise that supporting teachers' needs in the context of pediatric grief may eventually lead to their optimal ability to enact best practices for supporting grieving students' well-being.